2015
DOI: 10.1371/journal.pone.0131355
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Comprehensive Lifestyle Intervention in Patients Undergoing Chemotherapy with Curative or Palliative Intent: Who Participates?

Abstract: ObjectiveKnowledge about determinants of participation in lifestyle interventions in cancer patients undergoing chemotherapy, particularly with palliative intent, remains poor. The objective of the present study was to identify determinants of participating in a 12 month individualized, comprehensive lifestyle intervention, focusing on diet, physical activity, mental stress and smoking cessation, in cancer patients receiving chemotherapy with curative or palliative intent. The secondary objective was to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Over recent years in Mexico and around the world, there has been an increase in cancer research and a greater focus on new therapeutic strategies and detection methods [29]. It has been reported that a therapeutic and preventive effect can be achieved for several types of cancer with phytochemical derivatives of food or food sources, like capsaicin (peppers) [30], curcumin (curcuma) [31], resveratrol (grapes) [32], lycopene (tomatoes) [33], cinnamon essential oil [34], and others [35].…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years in Mexico and around the world, there has been an increase in cancer research and a greater focus on new therapeutic strategies and detection methods [29]. It has been reported that a therapeutic and preventive effect can be achieved for several types of cancer with phytochemical derivatives of food or food sources, like capsaicin (peppers) [30], curcumin (curcuma) [31], resveratrol (grapes) [32], lycopene (tomatoes) [33], cinnamon essential oil [34], and others [35].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many studies testing the effectiveness of interventions are threatened by high dropout rates, low adherence, and inaccuracy of self-reported tobacco use [75][76][77]. Furthermore, smoking is negatively associated with participation in lifestyle interventions [75]. These results illustrate the unique difficulties that health care professionals may face in terms of encouraging healthier behaviors in this population.…”
Section: Discussionmentioning
confidence: 99%
“…I CAN aims to increase adherence to healthy lifestyle behaviors, based on participants preferences and barriers, including a healthy diet [21], PA [2], stress management [22] and smoking cessation [23]. The intervention is described in detail previously [24].…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of medical and demographic variables is described in detail previously [24]. Tumor type was categorized into breast; colorectal ; prostate; and other cancer types (gastric, pancreas, gallbladder, urinary bladder, hepatic and origo incerta), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation